A taste for ATP: neurotransmission in taste buds - Finger, Thomas E.; Kinnamon, Sue C. (Frontiers in Cellular Neuroscience, 2013)
Not only is ATP a ubiquitous source of energy but it is also used widely as an intercellular signal. For example, keratinocytes release ATP in response to numerous external stimuli including pressure, heat, and chemical insult. The released ATP activates purinergic receptors on nerve fibers to generate nociceptive signals. The importance of an ATP signal in epithelial-to-neuronal signaling is nowhere more evident than in the taste system. The receptor cells of taste buds release ATP in response to appropriate stimulation by tastants and the released ATP then activates P2X2 and P2X3 receptors on the taste nerves. Genetic ablation of the relevant P2X receptors leaves an animal without the ability to taste any primary taste quality. Of interest is that release of ATP by taste receptor cells occurs in a non-vesicular fashion, apparently via gated membrane channels. Further, in keeping with the crucial role of ATP as a neurotransmitter in this system, a subset of taste cells expresses a specific ectoATPase, NTPDase2, necessary to clear extracellular ATP which otherwise will desensitize the P2X receptors on the taste nerves. The unique utilization of ATP as a key neurotransmitter in the taste system may reflect the epithelial rather than neuronal origins of the receptor cells.